2003
DOI: 10.1055/s-2003-40237
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Trial Comparing Endoscopic and Surgical Therapy for Chronic Pancreatitis

Abstract: Surgery is superior to endotherapy for long-term pain reduction in patients with painful obstructive chronic pancreatitis. Better selection of patients for endotherapy may be helpful in order to maximize results. Due to its low degree of invasiveness, however, endotherapy can be offered as a first-line treatment, with surgery being performed in case of failure and/or recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(155 citation statements)
references
References 21 publications
1
138
0
14
Order By: Relevance
“…Two randomized controlled studies provided significantly better pain management with surgical intervention involving a pancreatojejunostomy than with endoscopic treatment [66] [67]. 97% of patients with CP may suffer from abdominal pain, between 35% and 49% experience CBS, and between 6% and 12% have duodenal stenosis [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled studies provided significantly better pain management with surgical intervention involving a pancreatojejunostomy than with endoscopic treatment [66] [67]. 97% of patients with CP may suffer from abdominal pain, between 35% and 49% experience CBS, and between 6% and 12% have duodenal stenosis [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, two randomized trials have compared endoscopy with surgery in patients with CP [12,13]. Dite et al [13] included 140 patients with advanced CP (patients had CP for >5 years and were medically treated for their symptoms for at least 3 years) with PD obstruction and pain. Only 72 patients were randomized between endoscopic (without ESWL) and surgical treatment, and 68 patients refused due to a preference for one of the treatment arms.…”
Section: Head-to-head Comparison Of Endoscopic and Surgical Treatmentmentioning
confidence: 99%
“…In patients with an outflow obstruction of the pancreatic duct (PD) due to strictures, calculi or both, it is hypothesized that pain arises from increased ductal and parenchymal pressure [8,9,10,11]. The observation that endoscopic or surgical treatment of the PD obstruction relieves pain supports this hypothesis [12,13]. In addition, several other causes of pain have been suggested, such as ongoing inflammation, local complications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Experts believe that endoscopic management has an important role in patients [24] as a primary therapeutic measure in poor surgical candidates where medical management fails. Recent evidence by Díte et al [25] suggests that surgical outcomes were more durable than endoscopic therapy in patients with a dilated pancreatic duct (PD), stones and/ or strictures [25] . Cahen et al [26] recently reported better outcomes in pain control after surgery than with endoscopic intervention.…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…Díte et al [25] analyzed patients with CP secondary to large duct CP and compared endoscopic therapy to lateral pancreatojejunostomy procedure, and found that in the randomized and the non-randomized groups the results were similar. Moreover, on a five year follow up, patients in the surgery group were more likely to be pain free than in the endoscopic group.…”
Section: Surgical Optionsmentioning
confidence: 99%